Reply to Champagne's Comments on "Empirical Analysis of the Hugh Gray 'Nessie' Photograph" - Watson, Roland (Journal of Scientific Exploration, 2023)
The matter of Hugh Gray stating he saw no head versus what others see in his photograph is indeed a conflict requiring resolution. The simple solution is to discount all but Gray’s words as flawed. But this makes the assumption that eyewitnesses always perfectly describe what they see. Normally the imperfections of human observation and recall is used to reject all eyewitness testimony as inadmissible as evidence. But what I propose is that one can be an eyewitness to a large creature but still describe it imperfectly. Indeed, it should be the default position that every account has some degree of inaccuracy.